Exonerations in the United States 1989 Through 2003 - Gross, Samuel R. (2005)
On August 14, 1989, the Cook County Circuit Court in Chicago, Illinois, vacated Gary Dotson's 1979 rape conviction and dismissed the charges.1 Mr. Dotson-who had spent ten years in and out of prison and on parole for this conviction-was not the first innocent prisoner to be exonerated and released in America. But his case was a breakthrough nonetheless: he was the first who was cleared by DNA identification technology. It was the beginning of a revolution in the American criminal justice system. Until then, exonerations of falsely convicted defendants were seen as aberrational. Since 1989, these once-rare events have become disturbingly commonplace